Desert Plant Resources and Its Characteristics in Alxa Plateau - Song Zhaobin; Xin Zhiming; Zhu Yajuan (Shuitu baochi tongbao)
[Objective] The family and genus composition, life forms, water ecotypes, conservation plants, and resource plants among the plants in the Alxa Plateau desert area were analyzed in order to provide a basis for the rational development and utilization of desert plant resources, biodiversity protection, and ecological environment restoration on the plateau. [Methods] The composition of families and genera, life forms, water ecotypes, and special species of desert plants were analyzed through a vegetation survey and access to relevant information in the Alxa Plateau. [Results] There were 727 species of plants belonging to 284 genera and 70 families in the Alxa Plateau. Perennial herbs were the most common plant life forms, followed by annual herbs, biennial herbs, and shrubs. Mesophytes were the most abundant water ecotype, followed by xerophytes and mesoxerophytes. There were 24 national and autonomous regional protected plants, with 26 International Union for Conservation of Nature (IUCN) red list plants. Moreover, there were 210 medicinal plants and 186 forage plants. [Conclusion] In the desert area of the Alxa Plateau, Asteraceae, Chenopodiaceae, Fabaceae, and Poaceae were the dominant families, while Astragalus, Saussurea, and Artemisia were the dominant genera. Most plants were perennial herbs. Plants exhibited obvious xerophytic characteristics. There were many rare and endangered plant species, and there were abundant resource plants. In order to rationally use plant resources, it is necessary to manage and protect them according to their existing status and value type.